Pengaruh Kualitas Pelayanan, Literasi Keuangan, dan Mobile Banking Terhadap Kepuasan Anggota dan Kepercayaan Anggota BMT Al Fath Ikmi - Sari, Fanny Rahma (Jurnal Ilmiah Ekonomi Islam, 2024)
The growth of BMT Al Fath Ikmi, which is shown by increasing members and capital, is considered to have the potential for economic equality and prosperity in the community of South Tangerang City. Because BMT is a microfinance institution that can be said to be closest to the community, especially for the lower middle class. BMT Al Fath Ikmi has the potential to play a role in empowering society and helping reduce poverty through its financial services. This research will examine the influence on member satisfaction and trust of BMT members which has the potential to influence the community to become BMT members so that it can encourage economic equality and community welfare. This research uses quantitative methods with data collection techniques through observation and questionnaires. Primary data was processed using SmartPLS software version 3.2.8 with the results that service quality had a positive and significant effect on member satisfaction and member trust, financial literacy had a positive and significant effect on member satisfaction and member trust, mobile banking had a negative and no significant effect on member satisfaction. and member trust. From the results of the research that has been carried out, the quality of service must continue to be improved in providing services to its members. Financial literacy has a positive influence but still requires efforts to continue to introduce and provide knowledge to members and the community. Mobile banking is still not widely used by members so they cannot fully experience the convenience and benefits of this application.